Abonos orgánicos en el cultivo de cebolla roja (Allium cepa l.) En la finca glantina cantón Buena Fe - Mora Cevallos, Javier Carlos (2015)
This work was done in the canton Buena Fe, at the "Eglantine" geographically located 0 ° 57 '24' 'south latitude and 79 ° 27' 02 '' west longitude at an altitude of 100 meters, had a 90-day whose objectives were to evaluate the application of organic fertilizers in the cultivation of Oja onions (Allium cepa L.) at the "Eglantine" canton good faith and economic analysis of treatments. Three organic fertilizers including Agropesa compost, manure, worm castings and a control treatment were used, a total of 960 floors spread over four treatments and three repetitions, the experimental design was a complete block design was used random (DBCA), the variables were evaluated plant height and the number of sheets 30,60 and 90 days, weight and diameter of the bulb at the time of harvest and analysis of the respective treatments. Among the results are reported to the higher elevations of plant they occurred in the three types of fertilizers 12.00; 36.75 and 50.25 cm at 30, 60 and 90 days respectively, as many leaves, weight and diameter of the bulb bulb reported treatment with earthworm humus 60 to 90 days and harvest. Higher revenues and cost / benefit ratio is obtained in the treatment vermicompost $ 16.26 and 0.58. Allowing us to indicate that fertilizer earthworm humus should be used in the production of onions.